Dry film, cured product, and printed circuit board

By adopting a double-layer structure in the dry film and adjusting the photopolymerization initiator and colorant, the problems of uneven shape and high light absorption of the dry film on the concave-convex structure substrate are solved, and a cured product with uniform shape and high resolution is achieved, meeting the concealment and design requirements of the printed circuit board.

CN120722658APending Publication Date: 2025-09-30TAIYO HOLDINGS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510135176.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-27
Filing Date
2025-02-07
Publication Date
2025-09-30

AI Technical Summary

Technical Problem

In the prior art, when a dry film is formed on a substrate with a concave-convex structure, the film thickness of the resin layer deforms, resulting in an uneven shape of the cured product, making it difficult to achieve both resolution and concealment. In particular, the high light absorption of the black colorant makes photocuring difficult, and the desired anti-etching pattern cannot be formed.

Method used

A double-layer dry film structure is adopted, in which the thickness of the first layer is thicker than the second layer, the visible light transmittance of the first layer is higher than that of the second layer, and by adjusting the type and content of the photopolymerization initiator and colorant, the ultraviolet absorption coefficient of the second layer is ensured to be higher than that of the first layer, forming a cured product with good resolution and concealment.

Benefits of technology

The shape uniformity and resolution of the dry film and cured product are improved, taking into account both concealment and light curing effect, and avoiding resolution deviation and light absorption problems caused by film thickness deformation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120722658A_ABST
    Figure CN120722658A_ABST
Patent Text Reader

Abstract

The invention provides a dry film, a cured product and a printed circuit board. The dry film has good concealment and resolution and can form a cured product with a uniform shape. The solution of the present invention is a dry film having a first film and a resin layer formed on the first film and containing a curable resin composition, the resin layer having a first layer on the first film side and a second layer formed on the first layer, the thickness of the first layer being greater than the thickness of the second layer, and the thickness of the second layer being greater than the thickness of the first layer. The visible light transmittance of the first layer is higher than the visible light transmittance of the second layer, and when the thickness of the second layer is 10 [mu] m, the average visible light transmittance of the second layer is 50% or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a dry film, a cured product and a printed circuit board. Background Art

[0002] Printed circuit boards used in electronic devices have electronic circuit patterns formed on a substrate. Various components are mounted on the printed circuit boards by soldering or other methods.

[0003] When mounting components on a printed circuit board with exposed copper wires, there is a risk of wire breakage due to external forces, short circuits due to solder adhering to areas outside the circuit pattern, etc. Therefore, a solder resist layer is formed to protect the circuit pattern and prevent short circuits.

[0004] The solder resist layer is formed on the outermost layer of a printed circuit board. Therefore, the solder resist layer is sometimes required not only to protect the circuit but also to be highly invisible from the viewpoint of improving the design.

[0005] Highly concealed solder masks are made from curable resin compositions containing a high amount of colorant or a darker colorant. However, colorants, particularly black colorants, have high light absorption, which can prevent photocuring during resist pattern formation, leading to issues with achieving the desired resist pattern resolution.

[0006] In addition, as one of the means for forming the solder resist, dry film is utilized (for example, referring to patent document 1). After the resin layer of the dry film is laminated on the base material with the circuit pattern, patterning or curing is implemented, thereby the solder resist as described above can be formed on the printed circuit board.

[0007] Printed circuit boards mounted with QFP (Quad Flat Package) or SOP (Small Outline Package) ICs, which are flat-pack ICs, form barriers (hereinafter referred to as "solder dams") made of solder resist between electrodes to prevent solder bridges between pads during reflow soldering. To form solder resist using dry film on substrates with concave and convex structures such as pads, it is ideal for the resin layer to have a relatively low melt viscosity from the perspectives of filling and flatness (see, for example, Patent Document 2).

[0008] On the other hand, it was found that forming two layers of this type of resin suitable for dry film formation can cause deformation in the film thickness of the upper and lower layers in substrates with a concavo-convex structure, resulting in uneven shapes in the cured product. In particular, forming two layers of resin with different transmittances can significantly cause resolution variations due to this film thickness deformation.

[0009] Prior art literature

[0010] Patent Literature

[0011] Patent Document 1: Japanese Patent Application Laid-Open No. 1995-015119

[0012] Patent Document 2: International Publication No. 2017 / 122460 Summary of the Invention

[0013] (1) Technical issues to be resolved

[0014] The present invention has been made based on the above circumstances, and an object thereof is to provide a dry film having good concealing properties and resolution and capable of forming a cured product having a uniform shape, and a printed circuit board.

[0015] (2) Technical solution

[0016] That is, the dry film of the present invention is a dry film comprising a first film and a resin layer comprising a curable resin composition formed on the first film, and is characterized in that:

[0017] The resin layer includes a first layer on the first film side and a second layer formed on the first layer.

[0018] The thickness of the first layer is thicker than that of the second layer.

[0019] The visible light transmittance of the first layer is higher than that of the second layer.

[0020] When the thickness of the second layer is 10 μm, the average visible light transmittance of the second layer is 50% or less.

[0021] Furthermore, in the embodiment of the present invention, the curable resin composition preferably contains a carboxyl group-containing resin, a photopolymerization initiator, and a colorant.

[0022] Furthermore, in the aspect of the present invention, it is preferred that the ultraviolet absorption coefficient of the second layer is higher than that of the first layer, and the ultraviolet absorption coefficient of the second layer is 0.08 or greater.

[0023] In the embodiment of the present invention, it is preferred that at least one of the amount and type of the photopolymerization initiator contained in the curable resin composition forming the first layer differs from at least one of the amount and type of the photopolymerization initiator contained in the curable resin composition forming the second layer.

[0024] Furthermore, in the aspect of the present invention, it is preferred that the content of the photopolymerization initiator in the curable resin composition forming the first layer is smaller than the content of the photopolymerization initiator in the curable resin composition forming the second layer.

[0025] Furthermore, a cured product according to another embodiment of the present invention is characterized by being obtained by curing the resin layer of the dry film described above.

[0026] Furthermore, a printed wiring board according to another aspect of the present invention is characterized by comprising the above-mentioned cured product.

[0027] (3) Beneficial effects

[0028] According to the present invention, a dry film having good concealing properties and resolution, and capable of forming a cured product having a uniform shape, and a printed circuit board can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a schematic cross-sectional view of an example of the dry film of this embodiment.

[0030] Figure 2 It is a schematic cross-sectional view of a structure in which the dry film of this embodiment is disposed on a substrate.

[0031] Figure 3 Schematic cross-sectional view of the structure in the embodiment.

[0032] Figure 4 This is a schematic cross-sectional view of a structure during evaluation of resolution in Examples.

[0033] Figure 5 This is a schematic cross-sectional view of a structure subjected to evaluation of shape uniformity in an example. DETAILED DESCRIPTION

[0034] Hereinafter, the dry film, cured product, and printed wiring board of this embodiment will be described.

[0035] (Dry Film)

[0036] The dry film of this embodiment includes a first film and a resin layer, and further includes other members as needed.

[0037] <First Film>

[0038] The first film has a role of supporting the resin layer of the dry film, and is coated with a curable resin composition when the resin layer is formed.

[0039] In the present invention, the first film is a film that adheres to at least the resin layer when laminating a substrate such as a substrate to the resin layer of the dry film. The first film can be peeled off from the resin layer after laminating to the substrate, as described below. In this embodiment, it is preferably peeled off from the resin layer in the step after exposure.

[0040] As the first film, any known film can be used without particular limitation. For example, films made of thermoplastic resins such as polyester films such as polyethylene terephthalate and polyethylene naphthalate, polyimide films, polyamide-imide films, polypropylene films, and polystyrene films can be suitably used. Among these, polyester films are preferred from the perspectives of heat resistance, mechanical strength, and ease of handling. Furthermore, laminates of these films can also be used as the first film.

[0041] Furthermore, from the viewpoint of improving mechanical strength, the film formed of the thermoplastic resin is preferably a film stretched in a uniaxial direction or a biaxial direction.

[0042] When a thermoplastic resin film is used as the first film, a film having a specific surface morphology can be used by adding a filler to the resin during film formation (performing a kneading treatment); or performing a matte coating (coating treatment); or performing a blasting treatment such as sandblasting on the film surface; or performing hairline processing or chemical etching, etc.

[0043] The thickness of the first film is not particularly limited, and can be, for example, 10 μm to 150 μm.

[0044] <Resin layer>

[0045] The resin layer is formed on the first film and contains a curable resin composition. Here, the resin layer refers to a layer formed by applying the curable resin composition and drying it.

[0046] The resin layer includes a first layer on the first film side and a second layer formed on the first layer.

[0047] The first layer and the second layer of the dry film of the embodiment have the following relationship.

[0048] The thickness of the first layer is thicker than the thickness of the second layer

[0049] The visible light transmittance of the first layer is higher than that of the second layer

[0050] Furthermore, "high visible light transmittance" is synonymous with "light color of the cured product".

[0051] In the dry film, the boundary between the first layer and the second layer can be clear or fuzzy.

[0052] Here, the dry film of this embodiment will be described using the drawings. Figure 1 Schematic cross-sectional view of a dry film according to an embodiment. Figure 1 In the embodiment, the resin layer 13 is disposed on the first film 14. The resin layer 13 becomes a cured product when cured.

[0053] The resin layer 13 includes a first layer 11 and a second layer 12. The thickness T1 of the first layer is greater than the thickness T2 of the second layer, and the visible light transmittance of the first layer is higher than the visible light transmittance of the second layer.

[0054] Since the visible light transmittance of the first layer is higher than that of the second layer, the color of the first layer is lighter than that of the second layer, e.g. Figure 1 As shown, the color of the resin layer on the first film side (lower side) is lighter than the resin layer on the opposite side (upper side) to the first film.

[0055] In addition, when the dry film of this embodiment is arranged on a substrate, Figure 2 As shown, the second layer 12 is arranged in contact with the substrate 4 .

[0056] The thickness of the first layer is not particularly limited as long as it is thicker than the second layer, and can be appropriately selected depending on the intended purpose. For example, it is preferably 3 μm to 80 μm.

[0057] The thickness of the second layer is not particularly limited as long as it is thinner than the thickness of the first layer, and can be appropriately selected depending on the intended purpose. For example, it is preferably 1 μm to 20 μm, and more preferably 4 μm to 15 μm.

[0058] By making the thickness of the first layer thicker than the thickness of the second layer, a cured product having a uniform shape can be formed.

[0059] The visible light transmittance of the first layer is not particularly limited as long as it is higher than that of the second layer, and can be appropriately selected according to the purpose, but is preferably 50% to 80%, and more preferably 40% to 70%. When the visible light transmittance of the first layer is higher than that of the second layer, the resolution becomes better.

[0060] The visible light transmittance of the first layer is a value measured on the first layer alone when the thickness of the first layer is 10 μm.

[0061] The visible light transmittance of the second layer is 50% or less, preferably 5% to 50%, and more preferably 10% to 40%. When the visible light transmittance of the second layer is within this numerical range, resolution and concealment properties are improved.

[0062] The visible light transmittance of the second layer is a value measured on the second layer alone when the thickness of the second layer is 10 μm.

[0063] The visible light transmittance of the resin layer is defined as the average value of the transmittance within the range of 360 nm to 830 nm.

[0064] The specific measurement method is as follows: a curable resin composition is applied to a glass plate with a thickness of 1 mm so that the dry coating film becomes 10 μm, and dried at 80°C for 20 minutes. The entire surface is exposed at an optimal exposure dose using an exposure device equipped with a high-pressure mercury short-arc lamp. The surface is then developed using a 1% by mass sodium carbonate aqueous solution at a spray pressure of 0.2 MPa at 30°C for 60 seconds, and the cumulative exposure dose is 1,000 mJ / cm2 using a UV conveyor oven. 2 The film was irradiated with ultraviolet rays under the conditions of , and then cured by heating at 150° C. for 60 minutes, and the resulting cured product was used.

[0065] The resulting cured product was measured for a baseline within a wavelength range of 300 nm to 850 nm using an ultraviolet-visible-near-infrared spectrophotometer and integrating sphere (UV / VIS / NIR spectrometer V-570, manufactured by JASCO Corporation). Based on the measured baseline, the transmittance of the cured product within a wavelength range of 360 nm to 830 nm was measured. The measurement was performed at a scan rate of 400 nm / min and a scan interval of 1 nm.

[0066] The average value of the obtained measured values ​​within the range of 360 nm to 830 nm was defined as the measured visible light transmittance of the cured product of the curable resin composition.

[0067] The ultraviolet absorption coefficient of the second layer is preferably higher than that of the first layer. By setting the ultraviolet absorption coefficient of the first layer and the ultraviolet absorption coefficient of the second layer to have such a relationship, both resolution and concealment can be achieved.

[0068] The ultraviolet absorption coefficient of the first layer is not particularly limited as long as it is lower than that of the second layer, and can be appropriately selected depending on the intended purpose. It is preferably 0.01 to 0.07, and more preferably 0.02 to 0.06.

[0069] The ultraviolet absorption coefficient of the second layer is preferably 0.08 or more, more preferably 0.08 to 0.5.

[0070] The ultraviolet absorption coefficient can be measured by, for example, the following method.

[0071] The curable resin composition was applied to a 1 mm thick glass plate so that the thickness of the dried resin layer reached four levels (13 μm, 18 μm, 23 μm, and 28 μm) and dried at 80°C for 20 minutes. The absorbance of each resin layer at a wavelength of 365 nm was measured using an ultraviolet-visible-near-infrared spectrophotometer.

[0072] A plot was drawn with the thickness of the resin layer on the X-axis and the absorbance on the Y-axis. The UV absorption coefficient was calculated from the slope of the plot according to the Lambert-Beer law.

[0073] The resin layer may include layers other than the first layer and the second layer. The thickness, visible light transmittance, and ultraviolet absorption coefficient of the layer are not particularly limited as long as the effects of the dry film of this embodiment are not impaired, and can be appropriately selected according to the purpose.

[0074] <<Curable resin composition>>

[0075] The curable resin composition is not particularly limited as long as it has a property of curing and can be appropriately selected depending on the intended purpose. It preferably contains a carboxyl group-containing resin, a thermosetting component, a photopolymerization initiator, and a colorant, and further contains other components as needed.

[0076] <<<Carboxyl resin>>>

[0077] The carboxyl resin is a resin having a carboxyl group in the molecule, and various conventionally known resins can be used. By making the curable resin composition contain a carboxyl resin, it is possible to impart developability (alkaline developability) to the curable resin composition. In particular, from the perspective of photocurability or development resistance, a carboxyl photosensitive resin having an ethylenically unsaturated double bond in the molecule is preferred. The ethylenically unsaturated double bond is preferably derived from acrylic acid, methacrylic acid, or a derivative thereof.

[0078] When only a carboxyl group-containing resin having no ethylenically unsaturated double bond is used, a compound having multiple ethylenically unsaturated groups in the molecule, ie, a photopolymerizable monomer, described below, must be used simultaneously to make the composition photocurable.

[0079] Specific examples of the carboxyl group-containing resin include the following compounds (which may be either oligomers or polymers). These may be used alone or in combination of two or more.

[0080] (1) Carboxyl group-containing resins obtained by copolymerizing unsaturated carboxylic acids such as (meth)acrylic acid with unsaturated group-containing compounds such as styrene, α-methylstyrene, lower alkyl (meth)acrylates, and isobutylene.

[0081] (2) Carboxyl group-containing urethane resins produced by the polyaddition reaction of diisocyanates such as aliphatic diisocyanates, branched aliphatic diisocyanates, alicyclic diisocyanates, and aromatic diisocyanates with carboxyl group-containing diol compounds such as dimethylol propionic acid and dimethylol butyric acid, and diol compounds such as polycarbonate polyols, polyether polyols, polyester polyols, polyolefin polyols, acrylic polyols, bisphenol A-based alkylene oxide adduct diols, and compounds having phenolic hydroxyl groups and alcoholic hydroxyl groups.

[0082] (3) A carboxyl-containing photosensitive urethane resin produced by a polyaddition reaction of a diisocyanate with a partially anhydride-modified product of a reaction product of a bifunctional epoxy resin such as a bisphenol A epoxy resin, a hydrogenated bisphenol A epoxy resin, a bisphenol F epoxy resin, a bisphenol S epoxy resin, a bixylenol epoxy resin, a biphenyl diphenol epoxy resin, and a monocarboxylic acid compound having an ethylenically unsaturated double bond such as (meth)acrylic acid, a carboxyl-containing diol compound, and a diol compound.

[0083] (4) A carboxyl group-containing photosensitive urethane resin obtained by adding a compound having one hydroxyl group and one or more (meth)acryloyl groups in the molecule, such as a hydroxyalkyl (meth)acrylate, to the synthesis of the resin of (2) or (3) above, and performing terminal (meth)acrylation.

[0084] (5) A carboxyl group-containing photosensitive urethane resin obtained by adding a compound having one isocyanate group and one or more (meth)acryloyl groups in the molecule, such as an equimolar reaction product of isophorone diisocyanate and pentaerythritol triacrylate, to the synthesis of the resin of (2) or (3), and performing terminal (meth)acrylation.

[0085] (6) A carboxyl group-containing photosensitive resin obtained by reacting (meth)acrylic acid with a bifunctional or higher-functional (solid) epoxy resin and adding a dibasic acid anhydride to a hydroxyl group present in a side chain.

[0086] (7) A carboxyl group-containing photosensitive resin obtained by reacting (meth)acrylic acid with a polyfunctional epoxy resin obtained by epoxidizing the hydroxyl groups of a bifunctional (solid) epoxy resin with epichlorohydrin, and adding a dibasic acid anhydride to the generated hydroxyl groups.

[0087] (8) Carboxyl group-containing polyester resins obtained by reacting a dicarboxylic acid such as adipic acid, phthalic acid, or hexahydrophthalic acid with a bifunctional oxetane resin and adding a dibasic acid anhydride such as phthalic anhydride, tetrahydrophthalic anhydride, or hexahydrophthalic anhydride to the generated primary hydroxyl groups.

[0088] (9) A carboxyl group-containing photosensitive resin obtained by reacting a compound having at least one alcoholic hydroxyl group and one phenolic hydroxyl group in one molecule, such as p-hydroxyphenylethanol, with an unsaturated group-containing monocarboxylic acid, such as (meth)acrylic acid, with an epoxy compound having multiple epoxy groups in one molecule, and reacting a polyacid anhydride, such as maleic anhydride, tetrahydrophthalic anhydride, trimellitic anhydride, pyromellitic anhydride, or adipic anhydride, with the alcoholic hydroxyl group of the resulting reaction product.

[0089] (10) A carboxyl group-containing photosensitive resin obtained by reacting a reaction product obtained by reacting an unsaturated group-containing monocarboxylic acid with a compound having a plurality of phenolic hydroxyl groups in one molecule and an alkylene oxide such as ethylene oxide or propylene oxide, and reacting a polybasic acid anhydride with the reaction product.

[0090] (11) A carboxyl group-containing photosensitive resin obtained by reacting a reaction product obtained by reacting an unsaturated group-containing monocarboxylic acid with a compound having a plurality of phenolic hydroxyl groups in one molecule and a cyclic carbonate compound such as ethylene carbonate or propylene carbonate, and reacting a polybasic acid anhydride with the reaction product.

[0091] (12) A carboxyl group-containing photosensitive resin obtained by adding a compound having one epoxy group and one or more (meth)acryloyl groups in one molecule to the resins of (1) to (11).

[0092] In this specification, (meth)acrylate is a term that collectively refers to acrylate, methacrylate, and a mixture thereof, and other similar expressions are the same.

[0093] The acid value of the carboxyl group-containing resin is preferably 40 mgKOH / g to 150 mgKOH / g, and more preferably 50 mgKOH / g to 130 mgKOH / g. By setting the acid value of the carboxyl group-containing resin to 40 mgKOH / g or higher, alkaline developability becomes better. Furthermore, by setting the acid value to 150 mgKOH / g or lower, resolution can be improved.

[0094] The weight-average molecular weight of the carboxyl-containing resin varies depending on the resin backbone, but is generally preferably 2,000 to 150,000, and more preferably 5,000 to 100,000. By setting the weight-average molecular weight to 2,000 or greater, the non-stick performance and resolution can be improved. Furthermore, by setting the weight-average molecular weight to 150,000 or less, the developability and storage stability can be improved. The weight-average molecular weight (Mw) can be determined from the standard polystyrene conversion value obtained by gel permeation chromatography (GPC).

[0095] In the curable resin composition, the content of the carboxyl group-containing resin is preferably 20% to 60% by mass, more preferably 30% to 50% by mass, calculated as solids. By setting the content to 20% by mass or more, the strength of the cured product can be improved. Furthermore, by setting the content to 60% by mass or less, the viscosity becomes appropriate, and the printability is improved.

[0096] <<<Thermosetting ingredients>>>

[0097] Thermosetting components are not particularly limited as long as they cure by heating and can be appropriately selected depending on the purpose. Examples of thermosetting components include isocyanate compounds, blocked isocyanate compounds, amino resins, maleimide compounds, benzoxazine resins, carbodiimide resins, cyclocarbonate compounds, epoxy compounds, oxetane compounds, episulfide resins, and other commonly known components. These may be used alone or in combination of two or more. Among these, epoxy resins are preferred.

[0098] Examples of the epoxy resin include bisphenol A epoxy resin, bisphenol F epoxy resin, hydrogenated bisphenol A epoxy resin, brominated bisphenol A epoxy resin, bisphenol S epoxy resin, phenol novolac epoxy resin, cresol novolac epoxy resin, bisphenol A novolac epoxy resin, biphenyl epoxy resin, naphthalene epoxy resin, dicyclopentadiene epoxy resin, and triphenylmethane epoxy resin.

[0099] Regarding the content of the epoxy resin, when the carboxyl group-containing resin is contained in the curable resin composition, the epoxy group is preferably 0.3 to 2.5 equivalents, more preferably 0.5 to 2.0 equivalents, relative to 1 equivalent of the carboxyl group of the carboxyl group-containing resin, calculated on a solids basis. By setting the epoxy group content to 0.3 equivalents or more, the carboxyl group does not remain in the cured product, thereby improving heat resistance, alkali resistance, electrical insulation, etc. Furthermore, by setting it to 2.5 equivalents or less, the thermosetting component does not remain in the cured product, thereby improving the strength of the cured product.

[0100] <<<Photopolymerization initiator>>>

[0101] A photopolymerization initiator is contained to adjust the visible light transmittance of the dry film. By adjusting the visible light transmittance, the resolution and concealing properties can be improved.

[0102] The photopolymerization initiator is not particularly limited as long as it is a photopolymerization initiator commonly used in curable resin compositions, and can be appropriately selected according to the purpose, and a known photopolymerization initiator can be used.

[0103] As the photopolymerization initiator, for example, one or more photopolymerization initiators selected from the group consisting of oxime ester-based photopolymerization initiators having an oxime ester group, alkylphenone-based photopolymerization initiators, α-aminoacetophenone-based photopolymerization initiators, acylphosphine oxide-based photopolymerization initiators, and titanocene-based photopolymerization initiators can be used. Among these, it is preferred to include one or more photopolymerization initiators selected from the group consisting of α-aminoacetophenone-based photopolymerization initiators, acylphosphine oxide-based photopolymerization initiators, oxime ester-based photopolymerization initiators, and titanocene-based photopolymerization initiators, and it is more preferred to include an oxime ester-based photopolymerization initiator. It is further preferred that the second layer of the two resin layers include an oxime ester-based photopolymerization initiator or a titanocene-based photopolymerization initiator.

[0104] Examples of commercially available oxime ester photopolymerization initiators include Irgacure OXE01, Irgacure OXE02 (manufactured by BASF Japan Ltd.), N-1919, and NCI-831 (manufactured by ADEKA CORPORATION). Furthermore, photopolymerization initiators having two oxime ester groups in the molecule can also be used. Specifically, oxime ester compounds having a carbazole structure represented by the following general formula can be used.

[0105] [Chemical Formula 1]

[0106]

[0107] In the formula, X represents a hydrogen atom, an alkyl group having 1 to 17 carbon atoms, an alkoxy group having 1 to 8 carbon atoms, a phenyl group, a phenyl group (substituted by an alkyl group having 1 to 17 carbon atoms, an alkoxy group having 1 to 8 carbon atoms, an amino group, an alkylamino group having an alkyl group having 1 to 8 carbon atoms, or a dialkylamino group), or a naphthyl group (substituted by an alkyl group having 1 to 17 carbon atoms, an alkoxy group having 1 to 8 carbon atoms, an amino group, an alkylamino group having an alkyl group having 1 to 8 carbon atoms, or a dialkylamino group), and Y and Z represent a hydrogen atom, an alkyl group having 1 to 17 carbon atoms, an alkoxy group having 1 to 8 carbon atoms, a halogen group, a phenyl group, a phenyl group (substituted by an alkyl group having 1 to 17 carbon atoms, an alkoxy group having 1 to 8 carbon atoms, wherein Ar represents a bond, or an alkylene group having 1 to 10 carbon atoms, a vinylene group, a phenylene group, a biphenylene group, a pyridylene group, a naphthylene group, a thienylene group, a thienylene group, a furylene group, a 2,5-pyrrolediyl group, a 4,4'-stilbenediyl group, or a 4,2'-stilbenediyl group; and n represents an integer of 0 or 1.

[0108] Furthermore, examples of the carbazole oxime ester compound include compounds that can be represented by the following general formula.

[0109] [Chemical Formula 2]

[0110]

[0111] In the formula, R1 represents an alkyl group having 1 to 4 carbon atoms, or a phenyl group which may be substituted with a nitro group, a halogen atom, or an alkyl group having 1 to 4 carbon atoms.

[0112] R2 represents an alkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, or a phenyl group which may be substituted with an alkyl group or alkoxy group having 1 to 4 carbon atoms.

[0113] R3 may be linked via an oxygen atom or a sulfur atom and represents an alkyl group having 1 to 20 carbon atoms which may be substituted with a phenyl group, or a benzyl group which may be substituted with an alkoxy group having 1 to 4 carbon atoms.

[0114] R4 represents a nitro group or an acyl group represented by XC(=O)-.

[0115] X represents an aryl group which may be substituted with an alkyl group having 1 to 4 carbon atoms, a thienyl group, a morpholinyl group, a thiophenyl group, or a structure represented by the following formula.

[0116] [Chemical Formula 3]

[0117]

[0118] Examples of titanocene-based photopolymerization initiators include bis(cyclopentadienyl)diphenyltitanium, bis(cyclopentadienyl)titanium dichloride, bis(cyclopentadienyl)-bis(2,3,4,5,6-pentafluorophenyl)titanium, and bis(cyclopentadienyl)-bis(2,6-difluoro-3-(pyrrol-1-yl)phenyl)titanium. These can be synthesized as appropriate, or commercially available products can be used. Examples of commercially available products include JMT-784 (manufactured by Yueyang Kimoutain Sci-tech Co., Ltd.).

[0119] Examples of alkylphenone-based photopolymerization initiators include α-hydroxyalkylphenone-based initiators. Commercially available products include Omnirad 184, Darocur 1173, Irgacure 2959, and Omnirad 127 (2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propan-1-one) (all manufactured by IGM Resins).

[0120] Examples of α-aminoacetophenone-based photopolymerization initiators include 2-methyl-1-[4-(methylthio)phenyl]-2-morpholino-1-propanone, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butan-1-one, 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholino)phenyl]-1-butanone, and N,N-dimethylaminoacetophenone. Commercially available products thereof include Omnirad 907, Omnirad 369, and Omnirad 379 (all manufactured by IGM Resins).

[0121] Examples of acylphosphine oxide-based photopolymerization initiators include 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, and bis(2,6-dimethoxybenzoyl)-2,4,4-trimethyl-pentylphosphine oxide. Commercially available products include 2,4,6-trimethylbenzoyldiphenylphosphine oxide and Omnirad 819 (manufactured by IGM Resins).

[0122] The amount of photopolymerization initiators other than oxime ester-based photopolymerization initiators incorporated is preferably 0.01 to 30 parts by mass per 100 parts by mass of the carboxyl group-containing resin, calculated as solids content. A content of 0.01 parts by mass or greater improves the photocurability of the curable resin composition, making the cured product less susceptible to peeling and exhibiting excellent chemical resistance. On the other hand, a content of 30 parts by mass or less improves light absorption on the surface of the resin layer, minimizing degradation of deep-layer curability. A more preferred content is 0.1 to 20 parts by mass.

[0123] The amount of the oxime ester photopolymerization initiator incorporated is preferably 0.01 to 5 parts by mass per 100 parts by mass of the carboxyl group-containing resin, calculated as solids content. A content of 0.01 parts by mass or greater improves the photocurability of the curable resin composition, and also improves properties such as heat resistance and chemical resistance. On the other hand, a content of 5 parts by mass or less improves light absorption on the surface of the resin layer, and reduces the likelihood of a decrease in deep-layer curability. A more preferred content is 0.1 to 3.9 parts by mass.

[0124] The type and content of the photopolymerization initiator preferably satisfy the following conditions.

[0125] At least one of the amount and type of the photopolymerization initiator contained in the curable resin composition forming the first layer and at least one of the amount and type of the photopolymerization initiator contained in the curable resin composition forming the second layer may be the same, but preferably different.

[0126] Furthermore, it is more preferred that the content of the photopolymerization initiator in the curable resin composition forming the first layer is smaller than the content of the photopolymerization initiator in the curable resin composition forming the second layer.

[0127] By setting the type and content of the photopolymerization initiator to the above conditions, deep curability can be improved, and a curable resin composition having good resolution can be obtained.

[0128] <<<Colorant>>>

[0129] Colorants are included to adjust the visible light transmittance of the dry film. By adjusting the visible light transmittance, resolution and concealment can be improved.

[0130] The colorant is not particularly limited as long as it is a colorant commonly used in curable resin compositions and can be appropriately selected depending on the purpose. Conventional and known colorants such as black, red, blue, green, yellow, and white can be used, and any of pigments, dyes, and coloring materials can be used.

[0131] In addition, for black, only a black colorant may be used, or a colorant other than black may be mixed to produce black.

[0132] Examples of the black colorant include carbon black, zirconium nitride, and Pigment Black 1, 6, 7, 8, 9, 10, 11, 12, 13, 18, 20, 25, 26, 28, 29, 30, 31, and 32.

[0133] Examples of red colorants include monoazo colorants, disazo colorants, azo lake colorants, benzimidazolone colorants, perylene colorants, diketopyrrolopyrrole colorants, condensed azo colorants, anthraquinone colorants, and quinacridone colorants.

[0134] As blue colorants, there are phthalocyanine-based and anthraquinone-based colorants. As pigment-based colorants, compounds classified as pigments can be used. In addition, metal-substituted or unsubstituted phthalocyanine compounds can also be used.

[0135] Green colorants include phthalocyanine-based, anthraquinone-based, and perylene-based colorants. In addition, metal-substituted or unsubstituted phthalocyanine compounds can also be used.

[0136] Examples of yellow colorants include monoazo colorants, disazo colorants, condensed azo colorants, benzimidazolone colorants, isoindolinone colorants, and anthraquinone colorants.

[0137] Examples of white colorants include rutile or anatase titanium oxides, etc. In order to adjust the color tone, a colorant of purple, orange, brown, etc. may be added.

[0138] The content of the colorant is not particularly limited and can be appropriately selected depending on the intended purpose. The colorant in the first layer and the second layer preferably has the following content.

[0139] The content of the colorant in the first layer is preferably 0 to 30 parts by mass, more preferably 0 to 20 parts by mass, per 100 parts by mass of the carboxyl group-containing resin in terms of solid content. When the colorant content falls within this range, the resolution is improved.

[0140] The content of the colorant in the second layer is preferably 0.5 to 100 parts by mass, more preferably 1 to 80 parts by mass, per 100 parts by mass of the carboxyl group-containing resin in terms of solid content. When the colorant content is within this range, good concealing properties are achieved.

[0141] <<<Other ingredients>>>

[0142] The other components are not particularly limited as long as they are components commonly used in curable resin compositions and can be appropriately selected according to the purpose, and examples thereof include photopolymerizable monomers, fillers, and other additives. These may be used alone or in combination of two or more.

[0143] Photopolymerizable monomers are monomers having ethylenically unsaturated double bonds. Examples of such photopolymerizable monomers include conventionally known polyester (meth)acrylates, polyether (meth)acrylates, urethane (meth)acrylates, carbonate (meth)acrylates, and epoxy (meth)acrylates. Specifically, examples include alkyl acrylates such as 2-ethylhexyl acrylate and cyclohexyl acrylate; hydroxyalkyl acrylates such as 2-hydroxyethyl acrylate and 2-hydroxypropyl acrylate; monoacrylates or diacrylates of alkylene oxide derivatives such as ethylene glycol, propylene glycol, diethylene glycol, and dipropylene glycol; acrylamides such as N,N-dimethylacrylamide, N-hydroxymethylacrylamide, and N,N-dimethylaminopropylacrylamide; aminoalkyl acrylates such as N,N-dimethylaminoethyl acrylate and N,N-dimethylaminopropyl acrylate; and alkyl acrylates derived from hexyl glycol, trimethylolpropane, pentaerythritol, ditrimethylolpropane, dipentaerythritol, and trihydroxyethyl isocyanurate. Polyacrylates of polyols such as acrylates or their alkylene oxide adducts or ε-caprolactone adducts; polyacrylates of phenols such as phenoxyacrylate and bisphenol A diacrylate or their alkylene oxide adducts; acrylates derived from glycidyl ethers such as glycerol diglycidyl ether, trimethylolpropane triglycidyl ether, and triglycidyl isocyanurate; acrylates obtained by directly acrylated or urethane acrylated with diisocyanates, such as polyols such as polyether polyols, polycarbonate diols, hydroxyl-terminated polybutadienes, and polyester polyols, as well as melamine acrylates, and the corresponding methacrylates of the aforementioned acrylates. These may be used alone or in combination of two or more.

[0144] In addition, a photopolymerizable monomer can also be used as a reactive diluent.

[0145] The content of the photopolymerizable monomer is preferably 5 to 100 parts by mass per 100 parts by mass of the carboxyl group-containing resin, calculated as solids content. When the content is 5 parts by mass or greater, photocurability is improved, and pattern formation is less likely to occur in alkaline development after irradiation with active energy rays. On the other hand, when the content is 100 parts by mass or less, halation is less likely to occur, resulting in good resolution.

[0146] As the filler, known inorganic or organic fillers can be used, and barium sulfate, silica, and talc are particularly preferably used.

[0147] The content of the filler is not particularly limited and can be appropriately selected depending on the intended purpose.

[0148] <<Other additives>>

[0149] The curable resin composition of the present invention may further contain, as necessary, components such as a photoinitiator aid, a cyanate compound, an elastomer, a mercapto compound, a urethanization catalyst, a thixotropic agent, an adhesion promoter, a block copolymer, a chain transfer agent, a polymerization inhibitor, a copper inhibitor, an antioxidant, a rust inhibitor, a thickener such as organic bentonite or montmorillonite, at least one of silicone-based, fluorine-based, or polymer-based defoamers and leveling agents, a silane coupling agent such as an imidazole-based, thiazole-based, or triazole-based silane coupling agent, a flame retardant such as a hypophosphite, a phosphate ester derivative, or a phosphorus compound such as a phosphazene compound, and an organic solvent. These components may be known substances in the field of electronic materials.

[0150] <Method for preparing curable resin composition>

[0151] The method for preparing the curable resin composition is not particularly limited. For example, the composition can be prepared by blending the above-mentioned components in a predetermined ratio and then kneading or mixing them at room temperature using a kneading means such as a three-roll mill, a ball mill, a bead mill, or a sand mixer, or using a stirring means such as a super mixer or a planetary mixer. Furthermore, pre-kneading or pre-mixing may be performed as needed before the kneading or mixing.

[0152] <Other components>

[0153] The other members are not particularly limited as long as they are members generally used for dry films, and can be appropriately selected depending on the purpose. Examples thereof include a second film.

[0154] <<Second film>>

[0155] The second film is a film laminated on the surface of the resin layer to prevent dust from adhering to the surface of the resin layer. Specifically, it is a film that is peeled off from the resin layer before laminating the resin layer of the dry film to the substrate (described later) when laminating the substrate such as a substrate to the resin layer.

[0156] The second film can be made of, for example, polyethylene film, polytetrafluoroethylene film, polypropylene film, or surface-treated paper. Furthermore, the adhesion between the second film and the resin layer can be smaller than the adhesion between the resin layer and the second film. By making the second film's adhesion smaller than the first film, the second film can be peeled off without causing the first film to move.

[0157] The thickness of the second film is not particularly limited, and can be, for example, 10 μm to 150 μm.

[0158] <Dry film production method>

[0159] The curable resin composition is diluted with an organic solvent and adjusted to an appropriate viscosity, and is applied to the first film in a uniform thickness using a notch wheel coater, a knife coater, a lip coater, a rod coater, an extrusion coater, a reverse coater, a transfer roll coater, a gravure coater, a spray coater, an applicator, or the like, and is dried generally at a temperature of 50° C. to 130° C. for 1 minute to 30 minutes to form a resin layer, thereby obtaining a dry film.

[0160] The thickness of the applied curable resin composition is not particularly limited, but is generally appropriately selected within the range of 1 μm to 150 μm, preferably 5 μm to 60 μm, as the thickness of the resin layer after drying.

[0161] When the resin layer is produced by forming two layers containing two curable resin compositions having different compositions, the two layers may be produced simultaneously or layer by layer.

[0162] The simultaneous production of two layers means that the first film and the layer on the first film side are coated with respective curable resin compositions at the same time.

[0163] Layer-by-layer production refers to production by, for example, applying a curable resin composition forming one layer to a first film and drying it to form one layer, and then applying a curable resin composition forming another layer to the formed one layer and drying it.

[0164] Alternatively, the resin layers obtained by sequentially applying two different curable resin compositions to different first films and drying them may be laminated together using a laminator or the like.

[0165] (cured material)

[0166] The cured product of the embodiment is obtained by curing the resin layer of the dry film.

[0167] The size and shape of the cured product are not particularly limited and can be appropriately selected depending on the intended purpose.

[0168] The cured product can be produced by laminating the resin layer on the substrate using a laminator or the like so that the resin layer and the substrate are in contact with each other to form the resin layer on the substrate, and then curing the resin layer.

[0169] As a substrate, in addition to printed circuit boards or flexible printed circuit boards in which circuits are pre-formed using copper or the like, copper-clad laminates of all grades (FR-4, etc.) using materials such as paper phenolic, paper epoxy, glass cloth epoxy, glass polyimide, glass cloth / non-woven epoxy, glass cloth / paper epoxy, synthetic fiber epoxy, fluororesin·polyethylene·polyphenylene ether, polyphenylene ether·cyanate ester, etc. for high-frequency circuits, as well as metal substrates, polyimide films, polyethylene terephthalate films, polyethylene naphthalate (PEN) films, glass substrates, ceramic substrates, wafer plates, etc. can also be listed.

[0170] Lamination of the dry film to the substrate is preferably performed using a vacuum laminator or the like under pressure and heat. Using such a vacuum laminator allows the dry film to adhere closely to a circuit-formed substrate, even if the circuit substrate has irregularities on its surface. This prevents the incorporation of air bubbles and improves the ability to fill recessed areas on the substrate surface. The pressure is preferably between 0.1 and 2.0 MPa, and the heating is preferably between 40 and 120°C.

[0171] After the dry film is attached to the substrate, it is selectively exposed using active energy rays through a photomask having a predetermined pattern, and the unexposed portion is developed using a dilute alkaline aqueous solution (e.g., a 0.3-3% by mass sodium carbonate aqueous solution) to form a pattern of a cured product. In the case of a dry film, after exposure, the first film is peeled off from the dry film and developed, thereby forming a patterned cured product on the substrate. In addition, as long as it is within a range that does not damage the properties, the first film may be peeled off from the dry film before exposure, and the exposed resin layer may be exposed and developed. The cured product is then irradiated with active energy rays and then heat-cured (e.g., 100-220°C), or irradiated with active energy rays after heat-curing, or finally cured (formal cured) by heat-curing alone, thereby forming a cured product with excellent properties such as adhesion and hardness.

[0172] As an exposure machine for the above-mentioned active energy ray irradiation, any device equipped with a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, a metal halide lamp, a mercury short arc lamp, etc., and irradiating ultraviolet rays in the range of 350 to 450 nm can be used. A direct drawing device (for example, a laser direct imaging device that directly draws an image with a laser based on CAD data from a computer) can also be used. As a lamp light source or a laser light source of a direct drawing machine, a light source with a maximum wavelength falling within the range of 350 to 450 nm can be used. The exposure amount used for image formation varies depending on the thickness of the cured product, etc., and can generally be set to 10 to 1000 mJ / cm 2 , preferably set at 20~800mJ / cm 2 within the range.

[0173] As the above-mentioned development method, a dipping method, a shower method, a spray method, a brushing method, etc. can be used, and as the developer, an alkaline aqueous solution such as potassium hydroxide, sodium hydroxide, sodium carbonate, potassium carbonate, sodium phosphate, sodium silicate, ammonia, and amines can be used.

[0174] (Printed Circuit Board)

[0175] A printed wiring board according to one embodiment of the present invention comprises a cured product of the resin layer of the dry film.

[0176] The size and type of the printed circuit board are not particularly limited and can be appropriately selected depending on the intended purpose.

[0177] [Example]

[0178] Hereinafter, experiments conducted by the inventors of the present application will be described, but the present invention is not limited thereto.

[0179] <Preparation of carboxyl group-containing photosensitive resin>

[0180] Into an autoclave equipped with a thermometer, a nitrogen and alkylene oxide introduction device, and a stirring device, 119.4 parts by mass of a novolac-type cresol resin (Shonol CRG951, manufactured by Aica Kogyo Co., Ltd., OH equivalent: 119.4), 1.19 parts by mass of potassium hydroxide, and 119.4 parts by mass of toluene were charged. While stirring, the system was purged with nitrogen and heated to increase the temperature.

[0181] Then, 63.8 parts by mass of propylene oxide was slowly added dropwise at 125°C to 132°C and 0 kg / cm 2 ~4.8kg / cm 2 The reaction was allowed to proceed for 16 hours. The mixture was then cooled to room temperature, and 1.56 parts by mass of 89% phosphoric acid was added to the reaction solution to neutralize the potassium hydroxide. This yielded a propylene oxide reaction solution of a novolac-type cresol resin having a solids content of 62.1% and a hydroxyl value of 182.2 g / eq. To this propylene oxide reaction solution, an average of 1.08 mol of propylene oxide was added per equivalent of phenolic hydroxyl groups.

[0182] 293.0 parts by mass of the resulting propylene oxide reaction solution, 43.2 parts by mass of acrylic acid, 11.53 parts by mass of methanesulfonic acid, 0.18 parts by mass of methylhydroquinone, and 252.9 parts by mass of toluene were placed in a reactor equipped with a stirrer, a thermometer, and an air inlet tube. Air was blown in at a rate of 10 mL / minute, and the mixture was stirred at 110°C for 12 hours. The water produced by the reaction was formed into an azeotropic mixture with toluene, and 12.6 parts by mass of water was distilled off. The mixture was then cooled to room temperature, neutralized with 35.35 parts by mass of a 15% aqueous sodium hydroxide solution, and then washed with water. The toluene was then distilled off using an evaporator while being replaced with 118.1 parts by mass of diethylene glycol monoethyl ether acetate to obtain a novolac-type acrylate resin solution.

[0183] Next, 332.5 parts by mass of the obtained novolac-type acrylate resin solution and 1.22 parts by mass of triphenylphosphine were placed in a reactor equipped with a stirrer, a thermometer, and an air blowing tube. Air was blown in at a rate of 10 mL / minute. While stirring, 60.8 parts by mass of tetrahydrophthalic anhydride was slowly added. The mixture was reacted at 95°C to 101°C for 6 hours, cooled, and then taken out.

[0184] In this manner, a solution of a carboxyl group-containing photosensitive resin (hereinafter referred to as a carboxyl group-containing photosensitive resin) having a solid content of 65% and an acid value of 87.7 mgKOH / g of the solid matter was obtained.

[0185] (Examples 1 to 7, Comparative Examples 1 to 5)

[0186] <Preparation of Curable Resin Composition>

[0187] The materials were blended in the proportions shown in Table 1, premixed using a stirrer, and then kneaded using a three-roll mill to prepare curable resin compositions. The values ​​in the table are the contents in a solution including a solvent. The units in the table are parts by mass.

[0188] [Table 1]

[0189]

[0190] The details of the components other than the carboxyl group-containing photosensitive resin in Table 1 are as follows.

[0191] Thermosetting component (epoxy resin): EPICLON N-770 (manufactured by DIC Corporation)

[0192] Photopolymerization initiator 1: Irgacure OXE02 (manufactured by BASF Japan Ltd., oxime ester type)

[0193] Photopolymerization initiator 2: TOE-04-A3 (NIPPON CHEMICAL WORKS CO., LTD., oxime ester)

[0194] Photopolymerization initiator 3: 2,4,6-trimethylbenzoyldiphenylphosphine oxide (acylphosphine oxide system)

[0195] Photopolymerization initiator 4: Omnirad 369 (manufactured by IGM Resins BV, α-aminoacetophenone-based)

[0196] Photopolymerization initiator 5: JMT-784 (manufactured by Yueyang Kimoutain Sci-tech Co., Ltd., titanocene-based)

[0197] Blue colorant: CI Pigment Blue (pigment blue) 15:3

[0198] Yellow colorant: CI Pigment yellow 147

[0199] Red colorant: CI Pigment Red 149

[0200] Photopolymerizable monomer: Dipentaerythritol hexaacrylate (manufactured by Nippon Kayaku Co., Ltd.)

[0201] Filler: Barium sulfate (trade name: B-30, manufactured by SAKAI CHEMICAL INDUSTRY CO., LTD.)

[0202] Melamine: (manufactured by Nissan Chemical Corporation)

[0203] Solvent: Propylene glycol monomethyl ether acetate

[0204] Determining the optimal exposure

[0205] The following experiments were performed to determine the optimal exposure dose for the resin layer or dry film of the examples.

[0206] A copper-clad substrate (copper clad substrate) having a copper thickness of 18 μm was pretreated using an etchant (CZ-8100, manufactured by MEC COMPANY LTD.) to prepare a base material.

[0207] Next, the obtained curable resin composition was applied on a substrate so as to have a thickness of 10 μm after curing, and dried at 80° C. for 20 minutes to prepare a resin layer.

[0208] The dry film was laminated using a vacuum laminator in such a manner that the second layer (L2) was in contact with the substrate to produce a laminate such as Figure 3 The structure shown.

[0209] Next, the resin layer or the structure was exposed using an exposure device equipped with a high-pressure mercury short-arc lamp through a Stouffer 41-grid stepper. The first film was peeled off from the structure, and the exposure dose was determined to be the optimal exposure dose (mJ / cm2) when the pattern of the stepper remaining after development was performed for 60 seconds using a 1% by mass sodium carbonate aqueous solution at 30°C and a spray pressure of 0.2 MPa was 15. 2 ).

[0210] <Measurement of visible light transmittance>

[0211] Each of the resulting curable resin compositions was applied to a 1 mm thick glass plate as a substrate using an applicator to a thickness of 10 μm after curing, and then dried at 80°C for 20 minutes to form a resin layer. The resulting resin layer was fully exposed to the optimal exposure dose using an exposure device equipped with a high-pressure mercury short-arc lamp. The resulting resin layer was then developed for 60 seconds using a 1% by mass sodium carbonate aqueous solution at a spray pressure of 0.2 MPa at 30°C. The layer was then exposed using a UV conveyor oven at a cumulative exposure dose of 1,000 mJ / cm 2 The cured product of each curable resin composition was irradiated with ultraviolet light under the conditions of 100°C and then heated and cured at 150°C for 60 minutes to obtain a cured product of each curable resin composition. A UV-visible near-infrared spectrophotometer and an integrating sphere device (UV / VIS / NIRspectrometer V-570, manufactured by JASCO Corporation) were used to measure the baseline within 300 nm to 850 nm using the same glass plate as the glass plate coated with the curable resin composition. The transmittance of the cured product of each curable resin composition from the baseline within a wavelength of 360 nm to 830 nm was measured at a scanning speed of 400 nm / min and a scanning interval of 1 nm. The average value of the transmittance in this wavelength band was set as the visible light transmittance (%) of the cured product of the curable resin composition.

[0212] <Measurement of ultraviolet absorption coefficient>

[0213] The curable resin composition was applied to a 1 mm thick glass plate to achieve four different resin layer thicknesses (13 μm, 18 μm, 23 μm, and 28 μm) after drying, and then dried at 80°C for 20 minutes. The absorbance of each resin layer at a wavelength of 365 nm was measured using a UV / VIS / NIR spectrophotometer V-570 (manufactured by JASCO Corporation). A plot was created with the resin layer thickness on the X-axis and the absorbance on the Y-axis. The UV absorption coefficient was calculated from the slope of the plot according to the Lambert-Beer law.

[0214] [Table 2]

[0215]

[0216] <Dry film production>

[0217] Using the obtained curable resin compositions A to H, dry films were produced in the combinations shown in Table 3.

[0218] The curable resin composition forming the first layer (L1) was applied to a 38 μm thick polyester film (corresponding to the first film) using an applicator so that the thickness after drying was the thickness listed in Table 3, and then dried at 80°C for 10 minutes. Subsequently, the curable resin composition forming the second layer (L2) was applied to the first layer so that the thickness after drying was the thickness listed in Table 3, and then dried at 80°C for 10 minutes to prepare a dry film.

[0219] [Table 3]

[0220]

[0221] The obtained dry film was evaluated for hiding power, resolution, and shape uniformity as follows. The evaluation results are shown in Table 4.

[0222] <Concealment>

[0223] As a substrate, a printed circuit board with a circuit having a copper thickness of 25 μm, a line width of 100 μm, and a line spacing of 100 μm was used. The printed circuit board was pre-treated with an etchant (CZ-8100, manufactured by MEC COMPANY LTD.), and the resulting dry films were laminated using a vacuum laminator so that the second layer (L2) was in contact with the substrate to produce a Figure 3 The structure shown is formed by laminating the second layer 12 ( L2 ), the first layer 11 ( L1 ), and the first film 14 in this order on the substrate 4 .

[0224] The solder resist pattern was exposed on the fabricated structure using an exposure device equipped with a high-pressure mercury short-arc lamp at an optimal exposure dose. The first film was then peeled off and developed using a 1% by mass sodium carbonate aqueous solution at 30°C with a spray pressure of 0.2 MPa for 60 seconds to obtain a patterned structure. The UV conveyor oven was used to expose the structure at a cumulative exposure dose of 1,000 mJ / cm 2 The patterned structure was irradiated with ultraviolet light under the conditions of , and then heat-cured at 150° C. for 60 minutes to obtain an evaluation substrate.

[0225] The substrate was observed from the resin layer side to determine whether the copper circuit was visible by visual inspection and using an optical microscope (digital microscope, 50x magnification, VHX-6000, manufactured by KEYENCE CORPORATION). Concealment properties were evaluated based on the following evaluation criteria.

[0226] -Evaluation Criteria-

[0227] ◎: Circuit patterns are difficult to identify even with an optical microscope

[0228] ○: Although the circuit pattern is difficult to confirm visually, it can be confirmed using an optical microscope.

[0229] ×: The circuit pattern can be confirmed visually

[0230] Resolution

[0231] As a substrate, a copper-plated substrate without circuit formation was used. The substrate was pre-treated using an etchant (CZ-8100, manufactured by MEC COMPANY LTD.), and the resulting dry films were laminated using a vacuum laminator so that the second layer (L2) was in contact with the substrate to produce a film. Figure 3 The structure shown.

[0232] Using an exposure device equipped with a high-pressure mercury short-arc lamp and a negative mask for resolution evaluation with a solder dam width of 100 μm, the solder resist pattern was exposed on the fabricated structure at an optimal exposure dose. The first film was then peeled off and developed for 60 seconds using a 1% by mass sodium carbonate aqueous solution at a temperature of 30°C and a spray pressure of 0.2 MPa to obtain a solder resist pattern. The UV conveyor oven was used with a cumulative exposure dose of 1,000 mJ / cm 2 The patterned structure was irradiated with ultraviolet light under the conditions of , and then heat-cured at 150° C. for 60 minutes to obtain an evaluation substrate.

[0233] The maximum and minimum values ​​of the width of the cross section of the formed solder resist layer (solder resist dam width) were measured for the obtained evaluation substrate (refer to Figure 4), and the shape of the solder resist dam was evaluated based on the following evaluation criteria.

[0234] In addition, if the difference between the maximum and minimum values ​​of the solder resist dam width is large, the solder resist may peel off and cause a short circuit in the circuit, which can be said to be poor resolution.

[0235] -Evaluation Criteria-

[0236] ◎: The difference between the maximum and minimum dam widths is 10 μm or less

[0237] ○: The difference between the maximum and minimum dam widths exceeds 10 μm and is 30 μm or less

[0238] ×: The difference between the maximum and minimum dam widths exceeds 30 μm

[0239] Uniformity of shape

[0240] As a substrate, a circuit board having Cu pads with a thickness of 25 μm, a pad width of 200 μm, and a spacing of 150 μm was used. The substrate was pre-treated using an etchant (CZ-8100, manufactured by MEC COMPANY LTD.), and the resulting dry films were laminated using a vacuum laminator so that the second layer (L2) was in contact with the substrate to produce the following. Figure 3 The structure shown.

[0241] Using an exposure device equipped with a high-pressure mercury short arc lamp and a negative mask for resolution evaluation with a width of 100 μm and formed in the center between the Cu pads, the solder resist pattern was exposed on the fabricated structure at an optimal exposure dose. The first film was then peeled off and developed for 60 seconds using a 1% by mass sodium carbonate aqueous solution at a spray pressure of 0.2 MPa at 30°C to obtain a solder resist pattern. The UV conveyor oven was used with a cumulative exposure dose of 1,000 mJ / cm 2 The patterned structure was irradiated with ultraviolet light under the conditions of , and then heat-cured at 150° C. for 60 minutes to obtain an evaluation substrate.

[0242] The cross-sectional shape of the formed solder resist dam was observed at 10 points on the obtained evaluation substrate. Figure 5 As shown, for the measurement of solder dam width, the left and right sides are measured separately. Figure 5 The difference between the maximum width and the minimum width of the center line shown by the solid line at the middle distance (the reduction in the width of the dam on one side: Figure 5 Indicated by the bold line in the figure). When comparing the width reduction on one side of the solder resist dam, any dam with a difference of 5μm or more is considered deformed. The number of deformed dams is counted and the shape uniformity is evaluated based on the following evaluation criteria.

[0243] -Evaluation Criteria-

[0244] ◎: There is less than one dam with deformation

[0245] ○: There are 2 to 4 dams with deformation

[0246] ×: There are 5 or more dams with deformation

[0247] [Table 4]

[0248]

[0249] In the dry films of Examples 1 to 7, the thickness of the region opposite to the substrate (first layer) was greater than that of the region on the substrate side (second layer). The visible light transmittance of the first layer was higher than that of the second layer, and the average visible light transmittance of the second layer was 50% or less. Cured products of these dry films exhibited excellent concealing properties and resolution, and produced uniformly shaped products.

[0250] In contrast, the dry film of Comparative Example 1 had a thinner first layer than the second layer. The cured products of this dry film received a "Poor" rating for both resolution and shape uniformity, indicating that a uniform cured product could not be formed. The dry film of Comparative Example 2 had a lower visible light transmittance than the second layer, with the average visible light transmittance of the second layer exceeding 50%. The cured products of this dry film received a "Poor" rating for shape uniformity, indicating that a uniform cured product could not be formed. The dry film of Comparative Example 3 had an average visible light transmittance of the second layer exceeding 50%. The cured products of this dry film received a "Poor" rating for concealment. Furthermore, the dry films of Comparative Examples 4 and 5 were non-two-layer structures lacking a first and second layer. The cured products of these dry films received a "Poor" rating for resolution or concealment. These cured products failed to achieve both concealment and resolution.

[0251] As mentioned above, although the form for implementing this invention was demonstrated concretely, this invention is not limited to this, Various changes are possible within the range which does not deviate from the summary.

Claims

1. A dry film comprising a first film and a resin layer comprising a curable resin composition formed on the first film, characterized in that: The resin layer includes a first layer on the first film side and a second layer formed on the first layer. The thickness of the first layer is thicker than the thickness of the second layer, The visible light transmittance of the first layer is higher than the visible light transmittance of the second layer, When the thickness of the second layer is 10 μm, the average visible light transmittance of the second layer is 50% or less.

2. The dry film according to claim 1, wherein The curable resin composition contains a carboxyl group-containing resin, a photopolymerization initiator, and a colorant.

3. The dry film according to claim 1 or 2, wherein The ultraviolet absorption coefficient of the second layer is higher than that of the first layer, The ultraviolet absorption coefficient of the second layer is greater than or equal to 0.

08.

4. The dry film according to claim 1 or 2, wherein At least one of the amount and type of the photopolymerization initiator contained in the curable resin composition forming the first layer is different from at least one of the amount and type of the photopolymerization initiator contained in the curable resin composition forming the second layer.

5. The dry film according to claim 4, wherein The content of the photopolymerization initiator in the curable resin composition forming the first layer is smaller than the content of the photopolymerization initiator in the curable resin composition forming the second layer. 6 . A cured product obtained by curing the resin layer of the dry film according to claim 1 .

7. A printed circuit board comprising the cured product according to claim 6.

Citation Information

Patent Citations

  • Dry film type solder resist

    JP1995015119A